Volumetric comparison of positron emission tomography/computed tomography using 4′-[methyl-11C]-thiothymidine with 2-deoxy-2-18F-fluoro-D-glucose in patients with advanced head and neck squamous cell carcinoma. Issue 3 (March 2015) - Ito, Kimiteru; Yokoyama, Junkichi; Miyata, Yoko; Toyohara, Jun; Okasaki, Momoko; Minamimoto, Ryogo; Morooka, Miyako; Ishiwata, Kiichi; Kubota, Kazuo
Abstract : Objective: We prospectively compared the diagnostic value of PET/computed tomography (CT) findings using the tracers 4′-[methyl- 11 C]-thiothymidine ( 11 C-4DST) and 2-deoxy-2- 18 F-fluoro-D-glucose ( 18 F-FDG) in patients with head and neck squamous cell carcinoma (HNSCC). Patients and methods: Thirty-eight patients with advanced HNSCC underwent 11 C-4DST PET/CT and 18 F-FDG PET/CT before treatment. Maximum standardized uptake values (SUVmax ) were measured for both PET/CT studies; in addition, total lesion glycolysis (TLG) of 18 F-FDG PET/CT and total lesion proliferation (TLP) of 11 C-4DST PET/CT were measured. Absolute TLG and TLP values as well as values with various SUV thresholds were measured. All patients were followed up for 13.5±7.5 months (mean±SD) to monitor recurrence. Results: A statistically significant correlation was observed between the primary tumor SUVmax for 11 C-4DST PET/CT and 18 F-FDG PET/CT ( r =0.46, P <0.01). TLP values with SUV thresholds strongly correlated with TLG values relative to the same thresholds ( r =0.60–0.92, P <0.001). Nine of the 38 patients with post-treatment recurrence were identified. Receiver operating characteristic curves for TLG3.0 and TLP2.5 showed the highest prognostic ability for recurrence; the sensitivity and specificity of TLG3.0 were 89 and 72%, respectively, and the sensitivity and specificity of TLP2.5 were 89 and 55%, respectively. Conclusion: In patients with advanced HNSCC, the TLP of 11 C-4DST PET/CT strongly correlated with the TLG of 18 F-FDG PET/CT. Although there were no large differences between these values, the receiver operating characteristic curves of the absolute TLG had slightly better prognostic ability for recurrence.